The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/ajh.23397
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and impact of restless legs syndrome on patients with iron deficiency anemia

Abstract: Restless Legs Syndrome (RLS) a common, under-recognized disorder disrupts sleep and diminishes quality of life. Despite a clear relation between low peripheral iron and increased prevalence and severity of RLS, the prevalence and clinical significance of RLS in iron-deficient anemic (IDA) populations is unknown. In this study all new patients referred for anemia to a community-based hematology practice over a 1-year period (March 2011(March -2012 were included if they had IDA and no RLS treatment. Patients co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
121
0
10

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 202 publications
(140 citation statements)
references
References 19 publications
9
121
0
10
Order By: Relevance
“…In a study of Allen et al 34 , prevalence of clinically significant RLS (RLS sufferers) was 23.9% in 251 patients with IDA, nine times higher than the general population. In another study, the said ratio was reported as 40% 35 .…”
Section: Methodsmentioning
confidence: 95%
“…In a study of Allen et al 34 , prevalence of clinically significant RLS (RLS sufferers) was 23.9% in 251 patients with IDA, nine times higher than the general population. In another study, the said ratio was reported as 40% 35 .…”
Section: Methodsmentioning
confidence: 95%
“…Large population-based studies have shown that RLS affects up to 5 % to 15 % of individuals [7]. It is commonly observed in persons with peripheral neuropathy [8], and its prevalence is increased in systemic illnesses such as chronic kidney disease (CKD) [9], hypothyroidism [10], diabetes mellitus [11,12], and iron deficiency anemia [13]. Since both RLS [14] and cirrhosis [5,15] are known to be associated with sleep disturbance, one may expect an association between RLS and LC.…”
Section: Introductionmentioning
confidence: 99%
“…3,5,23 Although anemia is a known etiological factor causing to RLS, hemoglobin levels were similar of guides' recommended levels to hemodialysis patients. Even though hemoglobin levels were obtained lower than the renal transplant group, the lower frequency of RLS in transplant group shows other factors 47 predisposing rather than the anemia.…”
Section: Discussionmentioning
confidence: 96%